Personal Hygiene of Farmers in Besuk Village, Gurah District, Kediri Regency, 2018 - Nugraheni, Reny; Wardani, Siska Kusuma (Journal of Global Research in Public Health, 2018)
Background: In carrying out their work, farmers in Besuk Subdistrict, Gurah District, do not wear footwear and work in the fields without using gloves. Personal hygiene is still lacking. This can be seen from the habits of farmers who after working do not wash their hands before eating. Such conditions can facilitate the emergence of helminthiasis in farmers. Objective: Personal hygiene of farmers in Besuk Subdistrict, Gurah District, Kediri Regency Method: The type of research used is analytical survey method using cross sectional approach data collection using questionnaires and in-depth interviews. Results: Based on interviews and direct observations made in the village of Besuk, that the Personal Hygiene of the Besuk Village Farmers is not good as many as 58 respondents (96.67%) Conclusions and suggestions: Personal hygiene of Besuk Village farmers is not good. So it is necessary to conduct counseling for farmers to maintain personal hygiene especially after work and before eating by washing their hands and feet.